2008
DOI: 10.1016/j.icheatmasstransfer.2007.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation for natural convection by heated partitions in a cavity

Abstract: Entropy generation for natural convection in a partitioned cavity, with adiabatic horizontal and isothermally cooled vertical walls, is studied numerically by both a FORTRAN code and the commercially available CFD-ACE software. Effects of the Rayleigh number, the position of the heated partition, and the dimensionless temperature difference on the local and average entropy generation rate are investigated. Proper scale analysis of the problem showed that, while fluid friction term has nearly no contribution to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(49 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…The bottom and the roof sides are insulated. In this case, when H 0 = 0, then the enclosure structure limits to the rectangular shape that has been studied by Oliveski et al [18] and Famouri and Hooman [19]. 2.…”
Section: Description Of Models Geometriesmentioning
confidence: 97%
See 1 more Smart Citation
“…The bottom and the roof sides are insulated. In this case, when H 0 = 0, then the enclosure structure limits to the rectangular shape that has been studied by Oliveski et al [18] and Famouri and Hooman [19]. 2.…”
Section: Description Of Models Geometriesmentioning
confidence: 97%
“…In order to verify the present model, the enclosure was changed to the square cavity. The case as: L = H = 1.0, H 0 = 0 is like in Famouri and Hooman work [19]. We listed the conducted As seen from isotherms, it is observed that the rate of temperature variation at the bottom of the left wall and the top of the right wall is more than other spaces.…”
Section: Validation Of the Computational Schemesmentioning
confidence: 99%
“…Their results elucidated that at low Rayleigh numbers, the Marangoni number influence on the total entropy generation rises. Entropy generation for buoyancy-induced flow in a partitioned closed space, with adiabatic horizontal and isothermally cooled vertical walls, is studied numerically by Famouri and Hooman [11]. They presented the effects of fluid friction on entropy production is weak and the heat transfer irreversibility increases almost linearly with the Nu number and the temperature difference.…”
Section: Introductionmentioning
confidence: 99%
“…Variation the thickness of the wall near to cold boundary has more considerable enhancement effect than the wall near to hot boundary, especially in high Rayleigh numbers. Famouri and Hooman (2008) numerically studied entropy generation due to natural convection flow inside a rectangular enclosure with cold lateral walls, insulated horizontal walls and a hot plate inside the enclosure. Based on their results, generated entropy is increased by enhancement of the Rayleigh number.…”
Section: Introductionmentioning
confidence: 99%